The effect of various support materials on the catalytic activity of nickel in the low temperature steam reforming of methane - Monroy, Teddy G. (Animo Repository, 2006)
The effect support materials on the catalytic activity of Ni in the low temperature steam reforming of CH4 was studied using a fixed-bed quartz microreactor. The catalysis were prepared by loading Ni at 5% on y-Al2O3, SiO2, TiO2 and ZrO2 using both the wet and dry impregnation methods as applicable. Ni/ZrO2 gave the highest % CH4 conversion and H2 yield (H2 /CH4 ) at 5000C which can be attributed to the high oxygen mobility in the ZrO2 support. Catalyst deactivation due to carbon deposition was most pronounced in Ni/SiO2 where % CH4 conversion dropped after several hours on stream. The silanol bonds that formed on the surface of SiO2 when in contact with steam are known to encourage carbon deposition. Ni/TiO2 performed at par with Ni/y-Al2O3 at 5000C in terms of percent % CH4 conversion in spite of its lower number of acid and basic sites. However, Ni/TiO2 did not perform well at higher temperatures which may be due to the phase transformations that could have occurred as the temperatures were raised.